The Interplay between the Otsus Fund, Capital Expenditure, and Regional Economic Performance in Aceh Province - Herdiyana, Deni; Qadri, Resi Ariyasa; Sutarto, Sutarto; Kustiani, Nur Aisyah; Andriana, Nina (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 19 No 1 (2024)DO - 10.24843/JIAB.2024.v19.i01.p10, 2024)
This study aims to examine the impact of the Special Autonomy Fund on economic growth as measured by GRDP in the province of Nanggroe Aceh Darussalam (NAD). The research was conducted using the quantitative method of two-stage linear regression analysis. The independent variables used in this research model are General Allocation Funds (DAU), Revenue Sharing Funds (DBH), Special Allocation Funds (DAK), Special Autonomy Funds (Otsus Fund), and Regional Revenue (PAD) while the dependent variable is GRDP. Capital Expenditure is selected as an intervenning variable. The data used in this study is panel data from 23 regencies/cities in NAD Province for 5 years from 2015-2020. The recommendation from the research results is that the Otsus Fund should still be continued and extended where the Otsus Fund will end in 2028, because the results of the research found an indirect positive effect of the Otsus Fund on GRDP through Capital Expenditures at Lag-1. In the first stage of regression, it was found that DAK and Dana Otsus had a positive effect on Capital Expenditures, while DAU and DBH had no significant effect. In the second stage of regression, it was found that Capital Expenditures had a significant effect on GRDP.   Keywords:  General Allocation Funds, Revenue Sharing Funds, Special Allocation Funds, Special Autonomy Fund, Capital Expenditure, Economic Growth